2015
DOI: 10.1002/met.1491
|View full text |Cite
|
Sign up to set email alerts
|

Long-term runoff study using SARIMA and ARIMA models in the United States

Abstract: ABSTRACT:In this study, the ability of the seasonal autoregressive integrated moving average (SARIMA) and autoregressive integrated moving average (ARIMA) models was investigated for long-term runoff forecasting in the United States. In the first stage, the amount of runoff is forecasted for 2011 in each US state using the data from 1901 to 2010 (mean of all stations in each state). The results show that the accuracy of the SARIMA model is better than that of the ARIMA model. The relative error of the SARIMA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 251 publications
(90 citation statements)
references
References 21 publications
0
71
0
1
Order By: Relevance
“…have been among the most applied models in hydrology and have been used to predict hydrological variables till the present (e.g., PekĂĄrovĂĄ et al, 2009;Valipour, et al, 2013;Wang et al, 2015;Valipour, et al, 2015;Moeni et al, 2017). In general, however, applications of such time series models generally focus on modelling and predicting the mean behaviour or the first moment of the variable.…”
Section: Nonlinear Time Series Analysis In Hydrologymentioning
confidence: 99%
“…have been among the most applied models in hydrology and have been used to predict hydrological variables till the present (e.g., PekĂĄrovĂĄ et al, 2009;Valipour, et al, 2013;Wang et al, 2015;Valipour, et al, 2015;Moeni et al, 2017). In general, however, applications of such time series models generally focus on modelling and predicting the mean behaviour or the first moment of the variable.…”
Section: Nonlinear Time Series Analysis In Hydrologymentioning
confidence: 99%
“…ARIMA is a popular technique used for time series analysis and prediction [47][48][49][50][51][52][53]. This method has three components.…”
Section: Forecasting Modelsmentioning
confidence: 99%
“…Jia and Culver [28] using bootstrapped ANNs suggested that even a small set of periodic instantaneous observations of stage from a staff gauge, which can easily be collected by volunteers, can be a useful data set for effective hydrological modeling. M. Baareh et al [29] applied the ANN and AR models to the river flow forecasting problem. A comparative study of both ANN and the AR conventional model networks indicated that the ANNs performed better than the AR model.…”
Section: Introductionmentioning
confidence: 99%